Implementation Kanban method in Development System Information Web -Based Laundry Services at Happy Laundry Depok - Dini Hanifia (Jurnal Pengetahuan dan Pendidikan, 2025)
The study titled "Implementation of the Kanban Method in Developing a Web-Based Laundry Service Information System at Happy Laundry" focuses on improving transaction and financial data management. Currently, Happy Laundry records transactions manually using receipts, which are later transferred to a ledger. This manual system poses several challenges, including the risk of data loss, potential damage to records, and difficulties in performing monthly financial recapitulation. To address these issues, this research aims to design and develop a web-based laundry service information system by utilizing the Kanban method as the development approach. The Kanban method was chosen because it allows the development process to be monitored more effectively, ensures tasks are organized systematically, and provides clearer visibility of each stage of system design. The system is intended to digitize transaction recording, streamline financial management, and enhance overall operational efficiency. Findings from the research indicate that the implemented information system successfully supports the business operations of Happy Laundry. It enables more accurate and reliable transaction management, reduces human errors, and minimizes the risk of data loss. Overall, applying the Kanban method in developing the web-based system provides a structured approach that improves both the development process and the operational performance of the laundry service